A Strategy Change for Europe: Old Myths Versus New Roads - Karl Aiginger (Intereconomics, 2016)
Despite the substantial economic and political problems currently, it is important to recall that European integration has by and large been a success. However, restarting economic growth now should not follow the old trajectory, nor should it be built on old myths. It should start from a new vision with a much stronger emphasis on social and ecological investment.
Keywords: 330; Wirtschaftsintegration; EU-Staaten